2020
DOI: 10.1002/aid2.13239
|View full text |Cite
|
Sign up to set email alerts
|

Cold snare polypectomy for fundic gland polyps

Abstract: Fundic gland polyps (FGPs), the most common type of gastric polyps, are thought to be sporadic or associated with an inherited polyposis syndrome. FGPs associated with familial adenomatous polyposis (FAP) or attenuated FAP may have increased risk of dysplasia or malignancy. We evaluated the characteristics of FGPs and the endoscopic management with cold snare polypectomy of patients with fundic gland polyposis. We retrospectively analyzed data collected from our executive health management center on patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…HSP, by contrast, carries a small but more significant complication, DPPB, which is frequently related to damage to the submucosal layer caused by the electrocautery 20 . One recent study regarding CSP in gastric FGPs revealed no major complications such as delayed bleeding or perforation 21 . In the present study, DPPB did not occur in any patients who underwent CSP.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…HSP, by contrast, carries a small but more significant complication, DPPB, which is frequently related to damage to the submucosal layer caused by the electrocautery 20 . One recent study regarding CSP in gastric FGPs revealed no major complications such as delayed bleeding or perforation 21 . In the present study, DPPB did not occur in any patients who underwent CSP.…”
Section: Discussioncontrasting
confidence: 54%
“…20 One recent study regarding CSP in gastric FGPs revealed no major complications such as delayed bleeding or perforation. 21 In the present study, DPPB did not occur in any patients who underwent CSP. As CSP is considered to be a safe procedure, it could be promising treatment for gastric polyps.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations